(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines the problem of ensuring individual psychological safety in the digital age. The rapid expansion of digital technologies, social networks, artificial intelligence systems and algorithmic communication has created new opportunities for learning, self-expression and social participation. At the same time, the digital environment increases risks connected with stress, information overload, cyberbullying, manipulation, social comparison, privacy loss and emotional dependence on online platforms. The article analyzes psychological safety as a multidimensional condition that includes emotional stability, cognitive autonomy, digital literacy, self-regulation and protection from destructive informational influences. Special attention is paid to preventive strategies at the individual, family, educational and institutional levels. The study concludes that psychological safety in the digital era should be understood not as isolation from technology, but as the formation of a conscious, resilient and ethically protected personality.